The Role of Education in Improving Public Awareness of Taxpayers in UPT Region VI of The Regional Revenue Agency of Medan City - Lesmana, Angga; Ramadhani, Sri (PT Maju Malaqbi Makkarana, 2025)
Tax is the main source of income for the state to finance development and public services. However, public awareness of the obligation to pay taxes is still low. This is clearly seen in UPT Region VI of the Regional Revenue Agency (Bapenda) of Medan City, which causes a low level of public compliance in fulfilling tax obligations. This study aims to explore the role of education in increasing public awareness of taxpayers, as well as providing recommendations that can be implemented by Bapenda in an effort to improve tax compliance in the area. This study uses a qualitative approach, with a literature review approach. The results of the study show that tax education is very important to increase public awareness of the obligation to pay taxes. The education strategy implemented by UPT Region VI Bapenda Medan City includes the formation of a field team, providing taxpayer notification letters, education about taxpayers, assistance in registering as taxpayers, assistance in paying taxes, and tax socialization